Aspects of Youth Competencies in the 21st Century in the European Union - Pribac, Loredana; Ardelean, Dorina; Dudaș, Lavinia; Haiduc, Cristian; Anghelina, Andrei (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2017)
The aim of this article is to present the youth unemployment problem that the European Union countries are facing nowadays. To this end, we investigate the competencies and skills considered necessary in the 21 Century. We do this by presenting the competencies considered important by European employers versus Romanian employers. Not least, we reveal future directions in terms of skills required by employers.